HUBUNGAN DEPRESI DENGAN GANGGUAN FUNGSI KOGNITIF PASIEN STROKE - Mufidah, Nisfil; Wahyudi, Rahmad; Sulistyawati, Wiwin; Zahroh, Fatimatus (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Stroke is a leading cause of death and disability, and stoke survivors are at risk for cognitive impairment. Preliminary studies indicate a high incidence if cognitive impairment among stroke patients at ANNA Medika Madura Hospital. The purpose of this study is to examine the relationship between depression and cognitive function in patiens with stroke, The study utilitiez a cross-sectional design wiht a population of 94 stroke patients at ANNA Medika Madura Hospital, from which 76 respondents were selected using pusposive sampling. Spearman Rank Correlation used to data analyzed. The independent variabe is depression, and the dependent variable is cognitive function. Instrumen used in this study iclude the Hamilton Depression Rating Scale (HDRS) and MMSE. The analysis revealed that a minority of respondents, 28 individuals (36.8%), were not depressed. Spearman rank test, with a p value of 0.001, indicated a significant relationship between depression and cognitive performance. This suggests a significant relationship between depression and cognition in stroke survivors. Suggestions for researchers are expected to further expand research on cognitive function factors in stroke by adding several other variables